Electron-Positron Matter Waves as Oscillations of Minkowski Spacetime - Gritsunov, A. V. (My University, 2014)
An attempt is made to generalize the basic idea of the self-sufficient potential formalism in electrodynamics (interpretation of electromagnetic phenomena as natural or forced oscillations of the Minkowski spacetime treated as a distributed electromagnetic oscillating system) on the De Broglie waves. Both electrons and positrons are considered as excited modes (oscillations) of a distributed electronpositron oscillating system, not as "hard" particles. Thus, the matter waves are treated as real oscillations of the Minkowski spacetime, not as Born's "probability waves".
Keywords: Minkowski spacetime; distributed oscillatory system; de Broglie wave